The first Paleozoic stenopodidean from the Huntley Mountain Formation (Devonian–Carboniferous), north-central Pennsylvania. (November 2014) - Jones, Wade T.; Feldmann, Rodney M.; Schweitzer, Carrie E.; Schram, Frederick R.; Behr, Rose-Anna; Hand, Kristen L.
Abstract : A single specimen of a shrimp-like crustacean, Devonostenopus pennsylvaniensis, new genus and species is described from the Huntley Mountain Formation, which is Devonian–Carboniferous (Mississippian) in age. The specimen was collected in north-central Pennsylvania. Devonostenopus pennsylvaniensis is attributed to Stenopodidae. Co-occurrence of the specimen with pinnules of Archaeopteris halliana Goeppert, 1852, suggests that it is Devonian in age. Occurrence of a stenopodidean in the Devonian of North America is significant, as only three definitive decapods have been previously described from the Paleozoic and only two have been described from the Devonian. The earliest stenopodideans described to date are Cretaceous (Cenomanian and Santonian) in age. As such, Devonostenopus pennsylvaniensis extends the geologic range of Stenopodidea from Cretaceous to Late Devonian. Occurrence of a stenopodidean in the Devonian of North America, as well as the occurrence of the only two other known Devonian decapods in North America, suggests that Laurentia might have been a major area of endemism for Devonian decapods.